Discrete Sliding Mode Scheme for Uncertain Delay Time Systems using Delay Advanced Estimator - Y. P. Patil, H. G. Patel (International Journal of Control and Automation, 2020)
This article presents a delay advanced the estimator sliding mode control (DAE-SMC) method for discrete time-delay processes. The control law is design using a high-order system model with simple steps. A sliding surface is chosen as a function of the gain matrix with tracking error dynamics and a simple dominant pole location strategy is utilized to estimate the gain matrix. The robust performance against model perturbation and delay is the main advantage of the proposed DAE-SMC approach. The Lyapunov function stability analysis is given to prove the efficacy of control law. The simulation problem on the non-oscillatory scheme is presented to test the performance of the presented controller and compared with popular continuous-time sliding mode and conventional proportional-Integral-Derivative (PID) controller approaches.